Implementation of an Outreach Service for Population Administration Document Processing among Older Adults in Lumban Julu District, Toba Regency - Yolanda Agnesia Sinurat; Lince Magriasti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Population administration is a fundamental public service that plays a crucial role in ensuring citizens' civil rights. However, many older adults continue to face difficulties in obtaining population administration documents due to limited mobility, geographical barriers, inadequate transportation access, and socioeconomic constraints. To address these challenges, the Population and Civil Registration Office of Toba Regency has introduced the Jemput Bola service, a proactive outreach service designed to bring population administration services directly to vulnerable groups. This study aims to analyze the implementation of the Jemput Bola service for processing population administration documents for older adults in Lumban Julu District, Toba Regency, and to identify the factors influencing its implementation. A qualitative descriptive approach was employed. Data were collected through observations, in-depth interviews, and document analysis and were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the Jemput Bola service has improved older adults' access to population administration services by delivering services directly at the village level, thereby reducing geographical barriers and mobility limitations. The implementation of the program fulfills the dimensions of communication, resources, disposition, and bureaucratic structure as proposed by Edward III. Nevertheless, several challenges remain, including limited human resources, inadequate operational funding, insufficient facilities and infrastructure, and suboptimal interagency coordination. Therefore, strengthening institutional capacity, increasing budget allocation, and improving cross-sectoral coordination are essential to ensure that the Jemput Bola service is implemented more effectively, equitably, and sustainably.